A comprehensive approach of design and analysis of hybrid solar and pedal assisted electric three-wheeler - Md Shoaibur Rahman; Fahim Mahmud; Aditta Chowdhury (Discover Energy)
Abstract Electric three-wheelers consume a great deal of power causing load shedding in industrial and residential areas. This research investigates the feasibility of a solar-assisted electric three-wheeler for deployment in Bangladesh, integrating solar photovoltaic system and pedaling generator. This research focused on enhancing the energy efficiency and sustainability of electric three-wheelers using renewable energy reducing dependency on the national grid. The rooftop space of the vehicle is insufficient for the solar PV system, necessitating the whole surface area of the vehicle with a 600 W solar panel. Simulations for Dhaka, Cox’s Bazar, and Rangpur assessed the solar energy potential across Bangladesh. A 48 V solar PV array and a Maximum Power Point Tracking (MPPT) charge controller were designed to optimize battery charging, achieving converter efficiencies between 97%–99.2%. Partial shading significantly impacted performance, while tilt angle optimization suggested a 0 $$ ^{° }$$ ∘ tilt for moving vehicles and a 23 $$ ^{° }$$ ∘ tilt during idle periods from October to March for optimal energy capture. A pedaling DC generator was introduced to charge the battery during idle times without grid reliance. The simulations for energy harvesting estimated an annual energy production of approximately 820 kWh. The integration of these systems increased drag, reducing maximum speed and requiring additional power. 172.28 kWh annual additional energy consumption was calculated for the solar PV system and 200.75 kWh for the pedaling charger. The study found the solar-assisted system with enhanced efficiency and sustainability but the limited economic viability of the pedaling generator. In future, the system can be developed for other countries with different vehicles.